“Straszny Dwór” (Haunted Manor) guesthouse in Tatarów in the Hutsul region and its designer Jerzy Romaszkan - Czubiński, Jacek (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2017)
In the touristic and spa village of Tatarów in the Hutsul region, a very interesting guesthouse called “Straszny Dwór” (Haunted Manor) was established in the late 1930s. Jerzy Romaszkan – artist and amateur architect from Lviv was its designer. He was also the author of two other buildings: his own house and the house of Karol Kossak. Otton Liphardt, merchant from Warsaw, was the investor of “Straszny Dwór”. The building distinguishes itself in the region with its specific structure and composition of the façade. Its style refers among others to English Victorian-style and Cottage-style manors and the idea behind it is close to the assumptions of the Arts and Crafts movement.